HUBUNGAN ASUPAN LEMAK, PERSEN LEMAK TUBUH, SOMATOTYPE DENGAN KELINCAHAN ATLET SEPAKBOLA DIKLAT SALATIGA TRAINING CENTRE (STC) - Rizky Pratama Surya Saputra; Susi Tursilowati; Meirina Dwi Larasati; Sunarto Sunarto (Poltekkes Kemenkes Semarang, 2019)
Background: Agility is one of the important aspects to achieve maximum achievement. Player agility can be influenced by a combination of genetic factors, motivation, training, nutritional status, health status, and somatotype. In this study the things that will be examined in influencing agility are fat intake, percent body fat, and somatotype.Objective: To determine the relationship between fat intake, body fat percentage, and somatotype with the agility of soccer athletes in the Salatiga Training Center (STC) training.Method: This study was anstudy observational with adesign cross sectional. The sample used was all football athletes at the Salatiga Training Center (STC) and included in the inclusion criteria. The test used wasTest Chi Square to determine the effect of fat intake, percent body fat, somatotype on athlete's agility andtest Logistic Regression to determine how much influence fat intake, body fat percentage, and somatotype had on agility.Results: There was no relationship between fat intake and the agility of soccer athletes at the Salatiga Training Center (STC) training. There is no relationship between the percentage of body fat with the agility of soccer athletes at the Salatiga Training Center (STC) training. There is no relationship between somatotype and the agility of football athletes at the Salatiga Training Center (STC) training.Conclusion: There is no relationship between fat intake, percent body fat, and somatotype with the agility of soccer athletes at the Salatiga Training Center (STC) training.